Neurodevelopmental outcomes and comorbidities of children with congenital muscular torticollis: evaluation using the National Health Screening Program for Infants and Children database - Og Hyang Kim; Seung Won Lee; Eun Kyo Ha; Ju Hee Kim; Yun Hye Jo; Seongyeong Rhie; Man Yong Han; Kyu Young Chae (The Korean Pediatric Society, 2022)
Background Congenital muscular torticollis (CMT) is a common musculoskeletal disorder occurring at birth or in infancy. Purpose This study aimed to investigate the risk of comorbidities in CMT and explore the differences in neurodevelopmental outcomes between children who received physical therapy and those who did not. Methods Children with CMT born in 2008 and 2009 in Korea were included. CMT was defined as a primary diagnosis of congenital deformity of sternocleidomastoid muscle according to the International Classification of Diseases 10th revision. Here we investigated the associated neurological/musculoskeletal comorbidities of children with CMT versus those of the general population. We divided those with torticollis into treatment and nontreatment groups and assessed their developmental outcomes within both groups of children using the Korean-Ages and Stages Questionnaire (K-ASQ). Results Of the 917,707 children, 0.2% (n=1,719) were diagnosed with CMT. In children with torticollis, the prevalence of congenital hip deformities significantly increased to 4.5% (n=78). The prevalence of congenital head/spine deformities and other congenital malformations of the skull and facial bones increased to 2.6% (n=44), while the prevalence of congenital foot deformities was 2.4% (n=42). The risk ratio (RR) for delayed development based on the K-ASQ was higher for the total assessment (adjusted RR=0.97; 95% confidence interval, 0.93-0.99) in the CMT patients without physical therapy than in those with therapy. There was no significant intergroup difference in the assessment of each developmental area. Conclusion The prevalence of comorbid musculoskeletal deformities was higher in children with CMT than in the control group. The risk of developmental delay was higher in children who did not receive physical therapy than in those who did.